Healthcare Workers and COVID-19-Related Moral Injury: An Interpersonally-Focused Approach Informed by PTSD - D'Alessandro, Andrea M.; Ritchie, Kimberly; McCabe, Randi E.; Lanius, Ruth A.; Heber, Alexandra; Smith, Patrick; Malain, Ann; Schielke, Hugo; O'Connor, Charlene; Hosseiny, Fardous; Rodrigues, Sara; McKinnon, Margaret C. (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic has resulted in a still-unfolding series of novel, potentially traumatic moral and ethical challenges that place many healthcare workers at risk of developing moral injury. Moral injury is a type of psychological response that may arise when one transgresses or witnesses another transgress deeply held moral values, or when one feels that an individual or institution that has a duty to provide care has failed to do so. Despite knowledge of this widespread exposure, to date, empirical data are scarce as to how to prevent and, where necessary, treat COVID-19-related moral injury in healthcare workers. Given the relation between moral injury and post-traumatic stress disorder (PTSD), we point here to social and interpersonal factors as critical moderators of PTSD symptomology and consider how this knowledge may translate to interventions for COVID-19-related moral injury. Specifically, we first review alterations in social cognitive functioning observed among individuals with PTSD that may give rise to interpersonal difficulties. Drawing on Nietlisbach and Maercker 's 2009 work on interpersonal factors relevant to survivors of trauma with PTSD, we then review the role of perceived social support, social acknowledgement and social exclusion in relation to potential areas of targeted intervention for COVID-19-related moral injury in healthcare workers. Finally, building on existing literature (e.g., Phoenix Australia – Centre for Posttraumatic Mental Health and the Canadian Centre of Excellence – PTSD, 2020) we conclude with individual and organizational considerations to bolster against the development of moral injury in healthcare workers during the pandemic.